Morpho-physiological traits associated with drought survival in bi-specific perennial herbaceous swards - Volaire F. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Perennial grasslands provide numerous environmental benefits but their response to severe drought and therefore their sustainability in arid and Mediterranean areas have been little studied. Our work aimed to investigate the morpho-physiological traits associated with drought survival for bi-specific mixtures of perennial forage plants, and to test whether growth potential in spring was correlated with the capacity to survive subsequent summer droughts. Five cultivars (two of tall fescue, two of cocksfoot and one of Lucerne) were grown in monoculture and mixtures. Standard leaf functional traits and aerial biomass were assessed under non-limiting water supply in spring. In summer, under continuous severe drought, leaf water status, foliage senescence and plant survival were measured. Senescence of aerial tissues at the end of spring, associated with endogenous summer dormancy were the variables best correlated with drought survival. Specific leaf area under spring irrigation was also correlated with drought survival. These traits associated with dehydration tolerance strategies in pots should be completed with root traits contributing to dehydration delay in the field.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)